Habitat use, but not gene flow, is influenced by human activities in two ecotypes of Egyptian fruit bat (Rousettus aegyptiacus) - Centeno-Cuadros, A; Hulva, P; Romportl, D; Santoro, S; Stříbná, T; Shohami, D; Evin, A; Tsoar, A; Benda, P; Horáček, I; Nathan, R (Molecular ecology, 2017)
Understanding the ecological, behavioural and evolutionary response of organisms to changing environments is of primary importance in a human-altered world. It is crucial to elucidate how human activities alter gene flow and what are the consequences for the genetic structure of a species. We studied two lineages of the Egyptian fruit bat (Rousettus aegyptiacus) throughout the contact zone between mesic and arid Ecozones in the Middle East to evaluate the species' response to the growing proportion of human-altered habitats in the desert. We integrated population genetics, morphometrics and movement ecology to analyse population structure, morphological variation and habitat use from GPS- or radio-tagged individuals from both desert and Mediterranean areas. We classified the spatial distribution and environmental stratification by describing physical-geographical conditions and land cover. We analysed this information to estimate patch occupancy and used an isolation-by-resistance approach to model gene flow patterns. Our results suggest that lineages from desert and Mediterranean habitats, despite their admixture, are isolated by environment and by adaptation supporting their classification as ecotypes. We found a positive effect of human-altered habitats on patch occupancy and habitat use of fruit bats by increasing the availability of roosting and foraging areas. While this commensalism promotes the distribution of fruit bats throughout the Middle East, gene flow between colonies has not been altered by human activities. This discrepancy between habitat use and gene flow patterns may, therefore, be explained by the breeding system of the species and modifications of natal dispersal patterns.
Keywords: tok genů; Animals; Phenotype; Gene Flow; isolation by environment; Geography; circuit theory; Egypt; Chiroptera; lidé; isolation by resistance; fyziologická adaptace; Human Activities; Ecotype; zeměpis; Genetics, Population; isolation by adaptation; Microsatellite Repeats; Adaptation, Physiological; ekosystém; Ecosystem; lidské činnosti; fenotyp; zvířata; landscape genetics; Pteropodidae; mikrosatelitní repetice; populační genetika; ekotyp; Humans